Physiotherapy for cystic fibrosis in Australia and New Zealand: A clinical practice guideline*. Issue 4 (18th April 2016) - Button, Brenda M.; Wilson, Christine; Dentice, Ruth; Cox, Narelle S.; Middleton, Anna; Tannenbaum, Esta; Bishop, Jennifer; Cobb, Robyn; Burton, Kate; Wood, Michelle; Moran, Fiona; Black, Ryan; et al.
Abstract: Physiotherapy management is a key element of care for people with cystic fibrosis (CF) throughout the lifespan. Although considerable evidence exists to support physiotherapy management of CF, there is documented variation in practice. The aim of this guideline is to optimize the physiotherapy management of people with CF in Australia and New Zealand. A systematic review of the literature in key areas of physiotherapy practice for CF was undertaken. Recommendations were formulated based on National Health and Medical Research Council (Australia) guidelines and considered the quality, quantity and level of the evidence; the consistency of the body of evidence; the likely clinical impact; and applicability to physiotherapy practice in Australia and New Zealand. A total of 30 recommendations were made for airway clearance therapy, inhalation therapy, exercise assessment and training, musculoskeletal management, management of urinary incontinence, managing the newly diagnosed patient with CF, delivery of non‐invasive ventilation, and physiotherapy management before and after lung transplantation. These recommendations can be used to underpin the provision of evidence‐based physiotherapy care to people with CF in Australia and New Zealand.